Wonders of the world - Bertolazzi, Alberto; Ferrero, Giorgio; Manferto, Valeria; Romagnoli, Federica (Vercelli, Italy : White Star Publishers, 2008)
A collection of photographs profiling the most extraordinary places, landscapes, monuments, and works of art around the world.
Includes index.
Adult
Keywords: Architecture -- Pictorial works; Curiosities and wonders -- Pictorial works; Landforms -- Pictorial works; Architecture -- Pictorial works; Curiosities and wonders -- Pictorial works; Landforms -- Pictorial works